A comparison on HBsAg and HBsAb prevalence in patients with Down syndrome and other mentally retarded patients living in retarded children institutes in Tehran - Sahebjamei M. Associate Professor; Nik Bin B. Professor; Razavi Armaghanni N. Dentist (Tehran University of Medical Sciences, 2003)
Statement of Problem: The Prevalence of HBsAg, among patients with Down Syndrome (DS) has been"nreported higher than normal population. Living in institutes, comparing to home, leads to higher"nprobability of HBsAg prevalence."nAim: The purpose of the present study was to determine HBsAg prevalence in patients with DS and"ncompare it with other mentally retarded patients with similar conditions, and also with healthy population"nin Iran."nMaterials and Methods: One hundred patients, with average age of 12 years, living in five institutes in"nTehran, were chosen. Children with DS and other mentally retarded children were considered as the first"nand second groups, respectively (50 members in each group). Blood samples were taken and tested"n(ELLSA) to determine HBsAg and HBsAb titre. For statistical analysis, Chi- Square test was used."nResults: HBsAg was positive in 8% and 4% of DS and MR groups, respectively. HBsAb was seen in"n25% of DS, comparing to 32% of MR. The prevalence of HBsAg in retarded patients living in institutes"nwas higher than normal population of Iran (less than 3%), which was not statistically significant."nConclusion: Consideration of sterilization principles and infection control upon dental operations, in"nthese centers, are necessary. It is also suggested that these children, as a high- risk population, should be"nvaccinated against hepatitis B.